A numerical study: liquid sloshing dynamics in a tank due to uncoupled sway, heave and roll ship motions (Journal of Naval Architecture and Marine Engineering, 2013)
In order to explore the physics implicated with the sloshing phenomenon subjected to independent regular sway, heave and roll excitations of the liquid tank system, theoretical studies are carried out. Four liquid fill levels with static liquid depth, hs, to the length, l of aspect ratio (hs/l) 0.163, 0.325, 0.488 and 0.585, are considered. The energy spectra of sloshing oscillation, their qualitative assessment and the harmonics present in the sloshing oscillation are studied. Frequency Response amplitude has also been presented. The study reveals that sway excites a particular mode of sloshing (primary harmonic) by fulfilling the resonance conditions and also excites secondary modes. However, the roll motion excites the first mode of sloshing irrespective of the excitation frequencies. The heave motion excites the particular mode which is assumed as an initial perturbation.DOI: http://dx.doi.org/10.3329/jname.v10i2.16215